Interleukin 8 (CXCL8)-CXC chemokine receptor 2 (CXCR2) axis contributes to MiR-4437-associated recruitment of granulocytes and natural killer cells in ischemic stroke. (September 2018) - He, Qianyi; Shi, Xiaojuan; Zhou, Bin; Teng, Junfang; Zhang, Chaoqi; Liu, Shasha; Lian, Jingyao; Luo, Benyan; Zhao, Guoqiang; Lu, Hong; Xu, Yuming; Lian, Yajun; et al.
Highlights: CXCL8 in plasma and CXCR2 in peripheral leucocytes s of ischemic stroke patients were evaluated. CXCR2 expression positively correlated with granulocytes and NK cells. CXCL8 could attract CXCR2 positive granulocytes and NK cells. MiR-4437 cloud bind to the 3′UTR of CXCR2 mRNA and downregulated CXCR2 expression. Serum CXCL8 levels were associated with the infarct volume and functional outcomes in patients with ischemic stroke. Abstract: Granulocytes and natural killer (NK) cells have been linked to brain injury in ischemic stroke. However, their recruitment from peripheral leucocytes in stroke patients is not well understood. Here, the expression of the interleukin 8 (CXCL8) in plasma, and CXC chemokine receptor 2 (CXCR2) in peripheral leucocytes of patients with ischemic stroke were evaluated. Based on the results, CXCR2 expression positively correlated with granulocytes and NK cells, which were in turn attracted by CXCL8. The results also indicated that CXCR2 was a direct target of microRNA (miR)-4437, a negative regulator of CXCR2, which was downregulated in peripheral leucocytes from patients with ischemic stroke. Furthermore, serum CXCL8 levels were associated with the infarct volume and functional outcomes in patients with ischemic stroke. The results of the receiver operating characteristic curve analysis with an optimal cut-off value of 34 pg/mL indicated serum CXCL8 levels could be a prognostic indicator for ischemic stroke. In conclusion, these data highlighted the involvement of the CXCL8-CXCR2 chemotactic axis in the recruitment of granulocytes and NK cells in ischemic stroke. Furthermore, miR-4437 was suggested as a novel target for treating ischemic stroke, while the serum CXCL8 level could be a prognostic factor for ischemic stroke.